Confirmation of fifth Candida auris clade by whole genome sequencing. Issue 1 (31st December 2022) - Spruijtenburg, Bram; Badali, Hamid; Abastabar, Mahdi; Mirhendi, Hossein; Khodavaisy, Sadegh; Sharifisooraki, Joobin; Taghizadeh Armaki, Mojtaba; de Groot, Theun; Meis, Jacques F.
ABSTRACT: Candida auris has emerged globally as a multidrug-resistant pathogen causing outbreaks in health care facilities. Whole genome sequencing (WGS) analysis has identified four major clades, while earlier WGS data from a single Iranian isolate suggested the existence of a potential fifth clade. Here, we confirm the existence of this fifth clade by providing WGS data of another four Iranian isolates. These clade V isolates differed less than 100 single-nucleotide polymorphisms (SNPs) between each other, while they were separated from the other clades by more than 200, 000 SNPs. Two of these isolates were resistant to fluconazole and were found to harbour mutations in the TAC1b and ERG11 genes.